Use of bacille Calmette-Guérin in superficial bladder cancer. Issue 922 (1st August 2002) - Meyer, J-P; Persad, R; Gillatt, D A
Abstract : Intravesical bacille Calmette-Guérin (BCG) has been used by urologists for several years after its first reported use as a cancer therapy in the 1930s. Morales in 1976 described the usage of BCG as a once weekly intravesical instillation for six weeks; this is a treatment regimen that still exists today. Its success as a treatment depends on it being used appropriately. It is employed: (1) to treat carcinoma in situ or occasionally residual papillary tumours; (2) to reduce the number and frequency of recurrent high grade superficial tumours; and (3) to prevent disease progression (although this remains a controversial point, on which there is no consensus view). Unfortunately, the more widespread use of BCG is often limited due its high side effect profile. Present research is directed towards reducing its side effect profile, improving its efficacy, and understanding its exact mechanism of action, which is not fully understood.